2005
DOI: 10.1016/j.micromeso.2004.08.013
|View full text |Cite
|
Sign up to set email alerts
|

The effect of HCl treatment on water vapor adsorption characteristics of clinoptilolite rich natural zeolite

Abstract: In this study, water vapor adsorption properties of the clinoptilolite rich zeolite tuff, from Bigadic (Turkey), and its modified forms were examined. The modified forms were obtained by treating the tuff with HCl solutions (0.032, 0.16, 0.32, 1.6 or 5 M) at 25, 40, 75 and 100°C for 3 h. Infrared spectroscopy and water vapor adsorption were used for the characterization of the zeolites. Langmuir, BET and Dubinin-Raduschevich methods were applied in the analysis of water vapor adsorption data. Applications of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
62
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(70 citation statements)
references
References 14 publications
5
62
1
2
Order By: Relevance
“…Figure 2 shows asymmetric stretching increase from 1048.72 cm -1 (1) for raw zeolite to 1054.84 cm -1 and 1065.04 cm -1 for NaZ and dealuminated zeolite (ZA1), respectively. This shifting is caused by the leaching of Al from zeolite framework and changes on the bond strength and Si-O-Si angle [26]. Since Si has higher electronegativity than Al and Si-O bond is shorter than the Al-O bond, the decrease of Al content causes the increase of Si-O bond strength.…”
Section: Post-modification Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 2 shows asymmetric stretching increase from 1048.72 cm -1 (1) for raw zeolite to 1054.84 cm -1 and 1065.04 cm -1 for NaZ and dealuminated zeolite (ZA1), respectively. This shifting is caused by the leaching of Al from zeolite framework and changes on the bond strength and Si-O-Si angle [26]. Since Si has higher electronegativity than Al and Si-O bond is shorter than the Al-O bond, the decrease of Al content causes the increase of Si-O bond strength.…”
Section: Post-modification Treatmentsmentioning
confidence: 99%
“…Desilication can introduce mesoporosity to zeolite through alkaline treatment [10][11][12]. J.C. Groen in Huang (2014) suggested that for mordenite with optimal Si/Al ratios (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), mesoporosity was introduced after it was subjected to alkaline treatment (0.2 M NaOH at 65ºC for 30 min).…”
mentioning
confidence: 99%
“…These treatments enhance the pozzolanic reactivity of zeolites through de-alumination, resulting in a loss of crystallinity. Correspondingly, the silicon/aluminium ratio of untreated clinoptilolite significantly increases after treatment (Ates and Hardacre, 2012;Cakicioglu-Ozkan and Ulku, 2005;Elaiopoulos et al, 2010;Misaelides et al, 1996;Zhang et al, 2002). Furthermore, under alkali conditions and elevated temperatures, zeolites undergo eventual decomposition of their crystalline structure as a result of silicon leaching (Bonilla et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The properties of zeolite influence the adsorption process including chemical/structural makeup of the adsorbent, the Si/Al ratio, cation type, number and location. The properties of zeolite can be improved by changing pH, contact time, and adding surfactant for adsorption of various ions (6,11,12).…”
Section: Introductionmentioning
confidence: 99%